(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The study of any phenomenon, such as an economic phenomenon, a social phenomenon, a medical phenomenon, or any other phenomenon by researchers, requires the availability of DataThis is done by collecting data from its original sources for the purpose of Data analysisUsing one of the various statistical methods and obtaining conclusions that facilitate the role of the decision maker in reaching a conclusion Best decisionabout the phenomenon studied.